PERANCANGAN SISTEM INFORMASI AKADEMIK BERBASIS WEB (STUDI KASUS : SMP NOMMENSEN KOTA JAMBI) - Rubentus Hutapea; Ibnu Sani Wijaya; Roby Setiawan (Pusat Riset dan Inovasi Nasional, 2022)
SMP Nommensen Jambi City is one of the schools in Jambi City which is located on Jalan Barau-Barau 1 Pakuan Baru, South Jambi District, Jambi City. Currently Nommensen Junior High School in Jambi City is equipped with academic facilities, but has problems such as data processing which is still done conventionally which often results in errors in inputting academic data. The author plans to design a special website to solve problems at SMP Nommensen Jambi City by using PHP as an interface and MySQL as a storage database. The author will build a system that will be made using the waterfall method and using the UML system modeling. Then the system can produce output that is able to display admin data, teachers, students, classes, academic years, subjects, lesson schedules, announcements, and grades and is expected to make it easier to make reports so that administration and teachers can process academic data easily and help students obtain accurate and precise information.